Modification of spruce wood by UV-crosslinked PEG hydrogels inside wood cell walls - Ermeydan, Mahmut Ali (Elsevier Science Bv, 2018)
Chemical modification methods provide wood materials with longer service-life specifically for outdoor utilization by fixing impregnated reagents via covalent bonding into wood cell walls. In this study, poly(ethylene glycol) (PEG) diacrylate (PEGdA) was impregnated in spruce wood and cured via UV-polymerization to form poly(ethylene glycol) (PEG) hydrogel inside wood cell walls. The synthesis was performed in two steps: vacuum impregnation of PEGdA macromonomers and initiator into wood and subsequent crosslinking via UV-polymerization in water media. The resulting hydrogel modified wood cell walls (PEG-m-CW) were characterized by confocal Raman microscopy and spectroscopy, emission scanning electron microscopy, and equilibrium moisture content test. Results show that PEG hydrogels are formed deep inside the wood tissue structure: the polymer is distributed in both latewood and earlywood cell walls, and latewood lumina are filled due to macromonomer blockage. This process allows straightforward, highly practical synthesis of hydrogel in water media and has great potential as a modification method to eliminate specific disadvantages of wood.
Keywords: [No Keywords]